Multiple inflow pulsed arterial spin-labeling reveals delays in the arterial arrival time in minor stroke and transient ischemic attack. - MacIntosh, B; Lindsay, A; Kylintireas, I; Kuker, W; Günther, M; Robson, M; Kennedy, J; Choudhury, R; Jezzard, P (2010)
Our purpose was to use multiple inflow pulsed ASL to investigate whether hemodynamic AAT information is sensitive to hemispheric asymmetry in acute ischemia. The cohorts included 15 patients with acute minor stroke or TIA and 15 age-matched controls. Patients were scanned by using a stroke MR imaging protocol at a median time of 74 hours. DWI lesion volumes were small and functional impairment was low; however, perfusion abnormalities were evident. Prolonged AAT values were more likely to reside in the affected hemisphere (significant when compared with controls, P < .048). An advantage of this ASL technique is the ability to use AAT information in addition to CBF to characterize ischemia.